(untitled) (Research, Society and Development, 2020)
This study aims to verify in the scientific literature the impacts of domestic violence against women in the family context and the mental health of the victim. Therefore, a qualitative bibliographic research was carried out. The inclusion criterion was scientific articles published in Portuguese, with more relevant information for the research, and considerations were made regarding violence against women and its impacts on mental health. The results of the study indicate that there is a sociocultural context that considers gender inequality, favoring the practice of violence. In this regard, it should also be noted that in addition to the difficulties of the victim to try to abandon the violent context, there were numerous psychological impacts. It is concluded that through a survey of questions related to the theme of domestic violence, we sought to enable reflections and questions regarding the context in which violence occurs, such as damage to the mental health of victims, seeking a welcoming look in relation to woman raped, especially in health care.